Farmers’ Perception on the Sustainability of a Rubber- Based Agroforestry System as a Climate Change Adaptation Strategy in Agusan Del Sur and North Cotabato, Philippines - Furoc-Paelmo, Roselyn; Cosico, Russel Son A.; Cabahug, Rowena Esperanza D.; Castillo, Arnold Karl A.; Castillo, Arturo SA.; Visco, Roberto G. (2018)
This documentation research sought to evaluate the effectiveness of rubber-based agroforestry typologies as a climate change adaptation strategy in the major rubber producing regions in the Philippines, particularly in Agusan del Sur and North Cotabato. It focused on the understanding/perception of the RBAS farmer respondents on climate change and their account of its influence on the production system and their coping mechanisms. Among the farmer respondents, drought (El Niño), typhoon, strong winds, heavy rains/excessive rainfall, flash floods and landslides are among the common evidences of climate change. Generally, most of the adaptation strategies employed is through cultural management practices like minimized usage of inorganic fertilizer and chemical pesticides from Agusan del Sur farmer respondents while some of the farmer respondents in North Cotabato employed organic farming practices to adapt to climate change. For both provinces, farmer respondents particularly identified agroforestry and diversified farming system as an effective adaptation strategy. Results proved the potential of the rubber-based agroforestry system to evolve as a resilient farming practice to adapt to climate change vis-à-vis stable biological and economic productivity, controlled occurrence of pest and diseases and minimized detrimental effects of climate change on the agroforestry farm component as a whole.
Keywords: Climate change; Disaster resilience; Agroforestry